Effect of Science Technology Society Approach on Achievement Motivation in Biology of Secondary School Students of Kasaragod District - Smitha. E.T and , Dr. P. K. Aruna (IOSR Journal Of Humanities And Social Science (IOSR-JHSS), 2014)
Education is regarded as the potential instrument for social change and quality of education determined by the effectiveness of teacher and the teaching methods. The present study was conducted to investigate the effectiveness of Science Technology Society approach over activity oriented method of teaching on achievement motivation in Biology of Standard VII th students. True experimental design was used to investigate the present study. A sample of 90 students was selected randomly for the study.45 students were randomly selected to form an experimental group and another 45 were selected randomly for control group. The experimental group was taught through STS approach and the control group was taught through activity oriented method of teaching. The data were collected and analysed with the help of appropriate statistical techniques. The result revealed that STS approach is more effective than Activity oriented method in bringing Achievement motivation among Secondary School students.